2000
DOI: 10.2131/jts.25.specialissue_43
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Work to Evaluate Toxicity on Male Reproductive Organs by Repeated Dose Studies in Rats : 3)effects of Repeated Doses of Ethinylestradiol for 2 and 4 Weeks on the Male Reproductive Organs

Abstract: Male Sprague-Dawley rats were subcutaneously administered 0.3 and 3.0 mg/kg/day of ethinylestradiol for 2 and 4 weeks. Two weeks treatment decreased body weight gain, food consumption, absolute weights of testis, epididymis, prostate and seminal vesicle, and relative weights of epididymis, prostate and seminal vesicle. On the other hand, it increased absolute and relative weights of pituitary and adrenal glands, and induced atrophy of Leydig cells, degeneration/necrosis of pachytene spermatocytes, vacuolar deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…These discrepancies between the results from relative ratios and absolute counts demonstrate that the evaluation with absolute counts is essential in precisely assessing the cytotoxic changes in cases in which more than two different kinds of cells are affected simultaneously. The results from our FCM analysis are in accordance with the histopathological evaluation by Iwase et al (1995), Kaneto et al (1999b) Miyamoto et al (2000) and Kinomoto et al (2000). Kaneto et al (1999b) showed that dosages of 10 mg/kg EE resulted in a decrease of spermatocytes primarily, but spermatogonia was well-preserved for 2 weeks.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These discrepancies between the results from relative ratios and absolute counts demonstrate that the evaluation with absolute counts is essential in precisely assessing the cytotoxic changes in cases in which more than two different kinds of cells are affected simultaneously. The results from our FCM analysis are in accordance with the histopathological evaluation by Iwase et al (1995), Kaneto et al (1999b) Miyamoto et al (2000) and Kinomoto et al (2000). Kaneto et al (1999b) showed that dosages of 10 mg/kg EE resulted in a decrease of spermatocytes primarily, but spermatogonia was well-preserved for 2 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…Histopathological data was obtained from Higuchi et al (1995), Kaneto et al (1999a), Matsumoto et al (2000) and Watanabe et al (2000) for CP and Iwase et al (1995), Kaneto et al (1999b), Miyamoto et al (2000) and Kinomoto et al (2000) for EE. Only quantitative changes are shown in this table.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests minor effect of 1 mg/kg BW/day of EE administration on spermatogenesis, but highly significant effect at a dose of 10 mg/kg BW/day [15]. In another study, histopathological analysis reported a mild negative change in testis and epididymis at a dose of 3 mg/kg BW/day for 2 weeks [16]. We evaluated the impact of EE administration at different doses between 1–10 mg/Kg BW/day for two weeks to arrive at a dose significantly compromising spermatogenesis.…”
Section: Methodsmentioning
confidence: 94%
“…Male SD rats were randomly divided into 5 groups. The Group I (sham) represented control animals (N = 14) receiving 0.5% carboxymethylcellulose (CMC), group II (N = 7) III (N = 21) IV (N = 21) and V (N = 21) were administered EE (in 0.5% CMC) at 3 mg/kg BW/day for 14 days to compromise spermatogenesis [16]. After 14 th day, group II and 7 animals from group I were sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, low-dose HCB treatment increased the weight of the epididymis, an androgen-sensitive organ, at both time points. Exposure to testosterone propionate (Orgebin-Crist et al 1983) increases the weight of the epididymis, whereas ethinylestradiol (Kinomoto et al 2000) or flutamide (Toyoda et al 2000) exposure decreases it. The AGD is a developmental marker and is larger in males than females.…”
Section: Percent 3 H-r1881 Bound To Ar-lbdmentioning
confidence: 99%